The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1007/s10143-016-0781-0
|View full text |Cite|
|
Sign up to set email alerts
|

A prospective randomized multicenter phase I/II clinical trial to evaluate safety and efficacy of NOVOCART disk plus autologous disk chondrocyte transplantation in the treatment of nucleotomized and degenerative lumbar disks to avoid secondary disease: safety results of Phase I—a short report

Abstract: NOVOCART® Disk plus, an autologous cell compound for autologous disk chondrocyte transplantation, was developed to reduce the degenerative sequel after lumbar disk surgery or to prophylactically avoid degeneration in adjacent disks, if present. The NDisc trial is an ongoing multi-center, randomized study with a sequential phase I study within the combined phase I/II trial with close monitoring of tolerability and safety. Twenty-four adult patients were randomized and treated with the investigational medicinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 25 publications
(24 reference statements)
0
52
0
1
Order By: Relevance
“…This treatment is a combination of autologous disc chondrocytes and a self‐polymerizing hydrogel (http://clinicaltrials.gov study identifier NCT01640457) that is already being used clinically for articular cartilage repair in the knee. Preliminary results from the Phase I trial of this therapy indicate the risks of adverse events occurring are comparable to elective disc surgery …”
Section: Current Commercial Approaches For Cell‐based Disc Repair Andmentioning
confidence: 99%
“…This treatment is a combination of autologous disc chondrocytes and a self‐polymerizing hydrogel (http://clinicaltrials.gov study identifier NCT01640457) that is already being used clinically for articular cartilage repair in the knee. Preliminary results from the Phase I trial of this therapy indicate the risks of adverse events occurring are comparable to elective disc surgery …”
Section: Current Commercial Approaches For Cell‐based Disc Repair Andmentioning
confidence: 99%
“…However, in most cases, these therapeutic approaches remain in basic science or preclinical studies . Further development is also necessary within the context of a previously tested clinical approach …”
mentioning
confidence: 99%
“…7 Further development is also necessary within the context of a previously tested clinical approach. [8][9][10] The basis of successful preclinical development is establishing a representative animal model to serve as an analog for human spine pathology, for example, in the case of lumbar disc herniation. To date, several small animal preclinical studies have used mouse, rabbit, rat, and canine models to study IDD.…”
mentioning
confidence: 99%
“…Intradiscal PRP injection seems safe; however, its efficacy remains unclear . Chondrocyte transplantation studies showed some positive results in a small number of participants; further studies are needed to show efficacy . Experimental studies demonstrated cell leakage following injection with ectopic calcifications as a potential complication, thus motivating the need for a cell carrier to help enhance cell injections …”
Section: Available Clinical Treatments For Discogenic Painmentioning
confidence: 99%
“…(126)(127)(128)(129) Chondrocyte transplantation studies showed some positive results in a small number of participants; further studies are needed to show efficacy. (130)(131)(132) Experimental studies demonstrated cell leakage following injection with ectopic calcifications as a potential complication, thus motivating the need for a cell carrier to help enhance cell injections. (133,134) IVD repair techniques or implant biomaterials for annulus closures and NP replacement have the potential to repair the IVD, yet also create a risk for reherniation, which can cause nerve compression and the possibility of a recurrent painful condition or worsening of a condition.…”
Section: Regenerative Medicinementioning
confidence: 99%